Restaging Basilio's testament creating a life in dance; a review of the choreographic processes, inspiration, and motivation to re-create a phenomenal work - Chavez, Jhoy Anne Maverick F.
"This thesis presents the importance of Basilio's Testament in his life, which includes his choreographic processes, inspirations, and motivations and his enunciation of past or future choreographers on restaging it. It will show the processes involved and employed in Testament. The piece was first premiered in a festival in Hong kong and first performed by Dance Theatre Philippines. The music was entitled the Third Piano Concerto by Bela Bartok. It is a non-narrative piece, which deals with sociopolitical problems according to the choreographer. Conclusions are drawn from the actual re-staging of the piece and personal interviews done by the author. The thesis study traces the process taken by the author in restaging Basilio's work and explores the understanding of and appreciation for his unique aesthetic and choreographic intentions. Also, his choreographic processes are further shown to be enhanced by the experiences of the author as a dancer working with the piece created by Basilio along with her continued in-depth research and analysis into the nature of Basilio's genius and its impact on his craft. I hope that this research adds to the literature on the creative process, the choreographic process, the restaging process, and preserving legacies about dance pieces".